A novel method to reconstruct epithelial tissue using high-purity keratinocyte lineage cells induced from human embryonic stem cells. Issue 3 (1st February 2019) - Zhao, Houming; Shao, Yanxiong; Li, Hanqing; Zhou, Haiwen
ABSTRACT: The treatment of oral mucosa defect such as autologous oral mucosa caused by resection of oral mucosa carcinoma is still not ideal in clinical practice. However, Tissue engineering gives us the possibility to solve this problem. As we all know, Human embryonic stem cells (hESCs) have the ability to give rise to various cell types. We can take advantage of the totipotency of human embryonic stem cells to acquire keratinocytes. Directing the epithelial differentiation of hESCs can provide seed cells for the construction of epithelium tissue by tissue engineering. But, how to get high purity keratinocytes by induced stem cells then Applied to tissue engineering mucosa is an important challenge. We described a novel method to directly induce hESCs to differentiate into keratinocytes. Retinoic acid, ascorbic acid, and bone morphogenetic protein induced hESCs to differentiate into cells that highly expressed cytokeratin (CK)14. Our findings suggest that the retinoic acid, ascorbic acid and bone morphogenetic proteins induced hESCs to form high purity keratinocyte cell populations. In addition, we found that the highly pure keratinocyte populations reconstructed artificial tissue resembling epithelial tissue when inoculated in vitro on a biological scaffold.